2011
DOI: 10.1590/s0102-695x2011005000019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hydroalcoholic extract of Turnera diffusa Willd. ex Schult., Turneraceae, in tests for adaptogenic activity

Abstract: Abstract:The objective of the present study was to assess whether Turnera diffusa Willd. ex Schult., Turneraceae, (TD), plant known in popular medicine as tonic and aphrodisiac, has other effects that are characteristic of an adaptogen substance, such as improvement of the memory and reduction of the damage caused by stress. We carried out an initial screening to detect a possible toxicity of the plant. In that phase of the study we used tests of observational screening; evaluation of acute toxicity; measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…After one hour, the mice received sodium pentobarbital (50 mg/kg, i.p.) and the latency to sleeping and time between the loss and the recovery of the rightening reflex were recorded (Bezerra et al 2011).…”
Section: Pentobarbital Induced Sleeping Timementioning
confidence: 99%
“…After one hour, the mice received sodium pentobarbital (50 mg/kg, i.p.) and the latency to sleeping and time between the loss and the recovery of the rightening reflex were recorded (Bezerra et al 2011).…”
Section: Pentobarbital Induced Sleeping Timementioning
confidence: 99%
“…On the other hand, a great debate has been raised regarding the mechanism, effectiveness and extracts' polarity of Turnera diffusa as potential anti-ulcer treatment. Bezerra et al (2011) demonstrated that the hydroalcoholic extract of Turnera diffusa failed to suppress gastric ulceration induced by stress (immobilization and cold). While Gracioso et al (2002), observed a significant inhibition in the HCl/ethanol induced-gastric lesions of mice that received the hydroalcoholic and dichloromethanic extract of this plant (Gracioso et al, 2002;Piacente et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the loss of the righting reflex (sleeping time) was recorded. Animals were judged to be awake when they could right themselves up to three times (Bezerra et al, 2011).…”
Section: Methodsmentioning
confidence: 99%